The Influence of Motivation, Discipline, and Leadership on Village Apparatus Performance - Mariyani Mariyani; Ferry Khusnul Mubarok; Yuli Haryati; Johan Arifin (Quality Assurance Institute (LPM) State Islamic University Walisongo Semarang, 2021)
The performance of village officials is one of the main indicators of the quality of village government services. The performance of village officials is influenced by many factors, both internal and external. This study aimed to analyze whether motivation, work discipline, leadership, work motivation, and leadership of the village head influenced performance. The population of this research is all village officials in Karaskepoh, Doropayung, Jeruk, and Tuyuhan Villages, Pancur District, and Rembang Regency. The number of village officials is 30 people. In this study, all samples were used due to the small number of populations. The type of data used in this research is a quantitative approach with multiple regression analysis. This study concludes that work motivation, work discipline, leadership, and work for motivation, discipline, and leadership significantly affect performance in Karaskepoh, Doropayung, Jeruk, and Tuyuhan Villages Pancur District, Rembang Regency. Thus, in the future, to improve the performance of village officials, it is necessary to increase work motivation, increase discipline, and need leadership attitudes.